New York, New York: The Empire State of Mind - Al Makmun, Muhammad Taufiq; Ardianna Nuraeni, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper aims at reading the two songs entitled New York, New York and The Empire State of Mind to see how the city of New York is perceived and campaigned by the songs. It is an American popular cultural studies research discussing the two songs which are analysed as popular media works to deliver messages to the audiences. Inge’s theory on popular cultural works is employed to examine the form, function, and methods of evaluation in a way that the songs are treated as readable cultural texts. Semiotics is also employed as a relevant approach to interpret the data. In addition, Socio-cultural approach is applied in this study by considering American history that is useful to have a deeper discussion to examine how the city of New York is defined and spread by the media through the songs. The finding shows that the two popular songs see New York as a representation of America to hold the values of finding dreamland, conquering the wilderness, and achieving individual success in a modern materialistic capitalistic America. Released in two different eras, the songs are functioned as media voicing the American thoughts and feeling toward New York City as the today’s place of dream and reshaping the society itself as well.